1996
DOI: 10.1021/ie9602926
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Steady States in Homogeneous Separation Sequences

Abstract: In this article, multiple steady states are studied in sequences of interlinked columns commonly used to separate azeotropes in ternary homogeneous distillation. More specifically, two major separation schemes were concerned:  the intermediate entrainer scheme and the “boundary separation” scheme. On the basis of the results on multiplicities in single columns for the case of infinite reflux and infinite column length (infinite number of trays) similar criteria for separation sequences were developed. It is sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 18 publications
2
31
0
1
Order By: Relevance
“…Strategies for Identifying Multiple Steady States Using Aspen Plus. In Guẗtinger and Morari's work, 21 Aspen Plus was used to detect the multiple solutions in the intermediate entrainer separation sequences. Their results confirmed that the steady-state multiplicities may exist in the column operating at realistic conditions, and the two stable solutions on the LSS and HSS, respectively, were found.…”
Section: Steady-state Analysis and Simulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Strategies for Identifying Multiple Steady States Using Aspen Plus. In Guẗtinger and Morari's work, 21 Aspen Plus was used to detect the multiple solutions in the intermediate entrainer separation sequences. Their results confirmed that the steady-state multiplicities may exist in the column operating at realistic conditions, and the two stable solutions on the LSS and HSS, respectively, were found.…”
Section: Steady-state Analysis and Simulationmentioning
confidence: 99%
“…Thus, if the entrainer recycle is not closed, multiple steady states are expected for the first column of the direct or the indirect split sequence. Guẗtinger's work 21 proved that the existence of multiple steady states in intermediate entrainer separation sequence does neither depend on the external feed composition nor on the location of the azeotrope. Aspen Plus was utilized by Guẗtinger 21 to detect the multiple solutions in the acetone/benzene/n-heptane ternary system separation sequence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it has been systematically used for studying homogeneous and heterogeneous azeotropic distillation (Bekiaris et al, 1993;Müller and Marquardt, 1997;Müller, 1998). Further, it has successfully been applied to processes with more than one unit operation in a flow sheet (see e.g., Laroche et al, 1992;Esbjerg et al, 1998;Güttinger and Morari, 1996;Blagov et al, 2000;Nazanskii et al, 2001;Ulrich, 2002;Ulrich and Morari, 2003;Bonet et al, 2007). The stream table of a process resulting from ∞/∞ -analysis is, despite its inherent strong assumptions, often a good approximation of the stream table obtained from corresponding simulations based on the equilibrium stage model (Ryll et al, 2006;Grützner et al, 2007;Burger and Hasse, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Güttinger and Morari (1996) state that the general notion of multiplicity is that a system with specified variables that meet its degrees of freedom exhibits different solutions at steady-state. The multiplicity is called input multiplicity when two or more sets of input variables (flows) provide the same output condition.…”
Section: Introductionmentioning
confidence: 99%